International Governance : Protecting the Environment in a Stateless Society - Young, Oran R. (Book collections on Project MUSE., 1994)
How can the global environment be safeguarded in the absence of a world government? In the vanguard of efforts to address this critical question, Oran R. Young draws on environmental issues to explore the nature of international governance. Young's analysis invokes the distinction between "governance," a social function involving the management of interdependent individuals or groups, and "government," a set of formal organizations that makes and enforces rules.